Spatiotemporal microvascular changes following contusive spinal cord injury - Smith, Nicole J.; Doody, Natalie E.; Štěpánková, Kateřina; Fuller, Martin; Ichiyama, Ronaldo M.; Kwok, Jessica C. F.; Egginton, Stuart (Frontiers in Neuroanatomy, 2023)
Microvascular integrity is disrupted following spinal cord injury (SCI) by both primary and secondary insults. Changes to neuronal structures are well documented, but little is known about how the capillaries change and recover following injury. Spatiotemporal morphological information is required to explore potential treatments targeting the microvasculature post-SCI to improve functional recovery. Sprague-Dawley rats were given a T10 moderate/severe (200 kDyn) contusion injury and were perfuse-fixed at days 2, 5, 15, and 45 post-injury. Unbiased stereology following immunohistochemistry in four areas (ventral and dorsal grey and white matter) across seven spinal segments (n = 4 for each group) was used to calculate microvessel density, surface area, and areal density. In intact sham spinal cords, average microvessel density across the thoracic spinal cord was: ventral grey matter: 571 ± 45 mm−2, dorsal grey matter: 484 ± 33 mm−2, ventral white matter: 90 ± 8 mm−2, dorsal white matter: 88 ± 7 mm−2. Post-SCI, acute microvascular disruption was evident, particularly at the injury epicentre, and spreading three spinal segments rostrally and caudally. Damage was most severe in grey matter at the injury epicentre (T10) and T11. Reductions in all morphological parameters (95–99% at day 2 post-SCI) implied vessel regression and/or collapse acutely. Transmission electron microscopy (TEM) revealed disturbed aspects of neurovascular unit fine structure at day 2 post-SCI (n = 2 per group) at T10 and T11. TEM demonstrated a more diffuse and disrupted basement membrane and wider intercellular clefts at day 2, suggesting a more permeable blood spinal cord barrier and microvessel remodelling. Some evidence of angiogenesis was seen during recovery from days 2 to 45, indicated by increased vessel density, surface area, and areal density at day 45. These novel results show that the spinal cord microvasculature is highly adaptive following SCI, even at chronic stages and up to three spinal segments from the injury epicentre. Multiple measures of gross and fine capillary structure from acute to chronic time points provide insight into microvascular remodelling post-SCI. We have identified key vascular treatment targets, namely stabilising damaged capillaries and replacing destroyed vessels, which may be used to improve functional outcomes following SCI in the future.